Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/0253-7176.150820
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials Study in Children with Borderline Intellectual Functioning

Abstract: Background:Low general cognitive ability is a common cause for learning and academic difficulties. The present study was undertaken to objectively investigate the cognitive functioning of children having borderline intelligence using electrophysiological measures.Materials and Methods:The study was conducted on children having borderline intelligence (IQ: 70-85). The cognitive functioning of children was assessed using event-related potentials.Results:Significant prolongation of the latency of P200, N200, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…P300 and P2 reached the highest amplitudes in the average-intelligence group. This result is consistent with previous findings (Vaney et al, 2015) and may be explained by the type of cognitive task that is employed (Amin et al, 2015; McGarry-Roberts et al, 1992; Zhang et al, 1989). The task did not rely on great perceptual or discriminant ability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…P300 and P2 reached the highest amplitudes in the average-intelligence group. This result is consistent with previous findings (Vaney et al, 2015) and may be explained by the type of cognitive task that is employed (Amin et al, 2015; McGarry-Roberts et al, 1992; Zhang et al, 1989). The task did not rely on great perceptual or discriminant ability.…”
Section: Discussionsupporting
confidence: 93%
“…However, several others have reported a negative or no correlation between P300 amplitude and individual differences in intelligence (Houlihan, Stelmack, & Campbell, 1998; McGarry-Roberts, Stelmack, & Campbell, 1992; Robaey, Cansino, Dugas, & Renault, 1995). Vaney, Khaliq, and Anjana (2015) used a simple auditory oddball task and recorded ERPs in medium- and low-intelligence groups of children. They found lower P2 amplitudes in the more intelligent group and no significant differences in P300.…”
mentioning
confidence: 99%
“…It is thought that they may lag one to two years behind their peers of average intelligence. This may be due to impaired information processing which has an important role in the development of mental ability (Vaney et al, 2015). The authors, studied event-related potential, a non-invasive method, to study brain response to a variety of cognitive events, e.g.…”
Section: Neurodevelopment and Educationmentioning
confidence: 99%
“…In normal aging, age-related amplitude reduction, latency prolongation, and topographically more frontally oriented P300 have been consistently reported across studies [ 22 ]. Decreases in P300 amplitude and increases in latency more severe than those in normal aging have been reported in patients with dementia, psychiatric disorders, alcohol dependence, and traumatic brain injury (TBI), and in neurodevelopmental disorders [ 23 25 ]. The utility of the P300 latency as an objective measure in detecting changes in the cognitive performance for the application of testing therapeutics developed for neurodegenerative and neuropsychiatric disorders with associated cognitive deficits is discussed further in Section 5 .…”
Section: Event-related Potentials (Erps)mentioning
confidence: 99%
“…Meador and colleagues' study had a large influence on clinical practice when it demonstrated prolonging of P300 latency with antiepileptic drugs [ 93 ]. Indeed, the prolonged P300 latency has also been demonstrated in other indications with working memory deficits, including HD [ 26 ], transient ischemic stroke [ 94 ], intellectual disability [ 25 ], attention deficit hyperactivity disorder [ 95 ], and sleep deprivation [ 96 , 97 ]. Additionally, evaluation of ERP P300 in patients with TBI demonstrated increased P300 latency and reduced amplitude compared with healthy controls [ 24 , 98 ].…”
Section: Erp In Dementiamentioning
confidence: 99%